Kemampuan Pemecahan Masalah Tipe Higher Order Thinking Skill Ditinjau Dari Minat Belajar Siswa Kelas IX Tahun Ajaran 2020/2021 - Dwiana Permatasari; Sri Subarinah; Muhammad Turmuzi; Sripatmi Sripatmi (Griya Journal of Mathematics Education and Application, 2021)
The aim of this study is to describe the problem-solving ability of the ninth grade students with high, medium, and low interest in learning mathematics on math problems type Higher Order Thinking Skill (HOTS) in SMPN 2 MATARAM 2020/2021. This type of research is descriptive qualitative and the instruments used are mathematics questionnaire, the HOTS test, and an interview. The results of questionnaire via google form, there were 35 students of ninth grade has learning interest of high, medium, and low respectively 15, 16, and 4 students. Then, with stratified random sampling, 2 students were selected at each level to work on HOST test and interviews. The results of the data analysis from the ninth grade students of SMPN 2 Mataram 2020/2021 are the students with high interest in learning mathematics had very good at understanding problems, compiling plans, implementing plans, and reviewing. Students with moderate interest in learning mathematics are very good at understanding problems, good at planning, but quiet enough for implementing plans and reviewing. Meanwhile, students with low interest in learning mathematics are very good at understanding problems, good at planning, but lacking in implementing plans and very less in the reviewing them